Physiology of urination - KisilevichS., Leoncio (2015)
Voluntary, controllable, perceptible, painless and periodic urine, bladder evacuation is the result of a reflex triggered by the distended bladder, reflecting in coordination with muscle factors acting, entrustment to the bladder are obtained: filled, contain and expel urine at will.